2014
DOI: 10.20529/ijme.2014.059
|View full text |Cite
|
Sign up to set email alerts
|

A study of promotional advertisements of drugs in a medical journal: an ethics perspective

Abstract: The study assessed 54 advertisements of 145 different drugs, published over one year (from December 2011 to November 2012) in an Indian medical journal, circulated widely mainly among general practitioners (GPs). The ethical guidelines of the World Health Organization (WHO) and Organisation of Pharmaceutical Producers of India (OPPI) for medicinal drug promotion were applied. The brand name was mentioned in all advertisements (100% compliance both with the WHO and OPPI criteria) and the names of the active ing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…In concurrence with our results Nath S et al, demonstrated that majority of drug advertisements carried brand names (100%), contents of active ingredients (95.17%), dosage forms (81.37%). 10,11 Furthermore, it is seen that there appears to be greater adherence to the guidelines by the advertisements in this study as compared to Nath S et al, in regard to therapeutic uses (95% vs. 61.37%), side effects (22% Vs 1.37%), contraindications (22% Vs 1.37%) and major interactions (12% Vs 0%). 10 This gives a positive outlook as there appears to be a greater adherence to ethical guidelines.…”
Section: Discussioncontrasting
confidence: 38%
“…In concurrence with our results Nath S et al, demonstrated that majority of drug advertisements carried brand names (100%), contents of active ingredients (95.17%), dosage forms (81.37%). 10,11 Furthermore, it is seen that there appears to be greater adherence to the guidelines by the advertisements in this study as compared to Nath S et al, in regard to therapeutic uses (95% vs. 61.37%), side effects (22% Vs 1.37%), contraindications (22% Vs 1.37%) and major interactions (12% Vs 0%). 10 This gives a positive outlook as there appears to be a greater adherence to ethical guidelines.…”
Section: Discussioncontrasting
confidence: 38%
“…3 A similar trend is also seen in drug advertisements in medical journals published by many institutes and societies. 19 Main objective of this study was to critically evaluate various PDLs according to WHO criteria and identify flaws in drug promotion. In our study of PDL analysis, PDLs promoting FDCs products were more in comparison to single drug formulations.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of number of references to number of claims was not appropriate, similar observations were made in the study by Randhawa, et al 12 Only 46% of the DPLs had a complete address, same as quoted in the study by Nath S et al, which makes the traceability of the manufacturer a difficult task. 13 None of them mentioned about over dosage and other ingredients known to cause problems. This incomplete information can lead to irrational prescribing.…”
Section: Discussionmentioning
confidence: 99%